Reaching for power the shiʻa in the modern Arab world - Nakash, Yitzhak (Princeton University Press, 2006)
"This groundbreaking book addresses the crucial importance of Shi'is to the U.S. endeavor. Yet it also alerts readers to the strong nationalist sentiments of Shi'is, underscoring the difficult challenge that the United States faces in attempting to impose a new order in the Middle East."--Jacket